The Impact of the SIGNAL (National Digital Samsat) Application on Motor Vehicle Taxpayer Compliance and Its Implications for Local Own-Source Revenue at the Samsat UPTB I Palembang Office - Maratul Fadillah; Aris Munandar; Andini Putri Utari (Economics and Digital Business Review, 2026)
The implementation of the SIGNAL (Samsat Digital Nasional) application represents a strategic milestone in modernizing Motor Vehicle Tax administration. This study examines the impact of SIGNAL usage on taxpayer compliance and its subsequent implications for Local Genuine Revenue (PAD) at the UPTB I Samsat Office in Palembang. Utilizing a quantitative approach with a sample of 100 taxpayers, the data was analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings demonstrate that the utilization of the SIGNAL application has a positive and significant effect on increasing taxpayer compliance. Furthermore, higher compliance levels are proven to significantly boost PAD achievements. Mediation tests confirm that taxpayer compliance acts as an intervening variable that bridges the gap between digital service effectiveness and the optimization of regional income. These results underscore that the digital transformation of tax services effectively enhances public awareness and participation in fulfilling tax obligations. Consequently, strengthening digital literacy and expanding the socialization of the SIGNAL application are essential to support sustainable regional fiscal independence. This study suggests that leveraging information technology is key to fostering a modern, transparent, and efficient taxation ecosystem.